Indonesian Senior High School Students' Activities in Learning Narrative Text within a Reading Comprehension Classroom - Banar, Dimas Priagung; Satrio, Nurman Bagus (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2022)
The research was conducted to describe students’ activities in reading comprehension classroom, especially in learning narrative text. A qualitative descriptive approach was used in this research. To collect the data, observation, interview, and test were employed to gather the data of students’ activities in learning narrative text within reading comprehension class. Data from observation and interview were analyzed descriptively, while data from test were first calculated to find the mean of the score, then they were used to analyzed the minimum criteria of achivement (Kriteria Ketuntasan Minimun/ KKM). Based on the observation, it yielded that the student activities in learning narrative text were 1) identifying difficult vocabulary, 2) translating the vocabulary over dictionary, 3) asking teachers or peers to comprehend meaning, 4) writing the correction in the paper, 5) reviewing initial analysis, 6) asking teachers or peers for main ideas and supporting detail, 7) giving overall corrections, and 8) summarizing. Furthermore, the test result showed that the student's scores are different from other students such as five students getting a good score, twelve students getting enough score, and three students getting less score. The students' average score of reading is 73,75 which was above KKM. The interview result discovered that most of them thought that the eight reading activities above gave much influences on students understanding on reading narrative texts and their ability in completing the test. The research conclusion was the eight reading activities found were relevant because most students’ reading comprehension were above KKM.